2023
DOI: 10.1161/atvbaha.122.318748
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tissue Factor Inhibition for Thromboprophylaxis in COVID-19: Primary Results of the ASPEN-COVID-19 Trial

Abstract: BACKGROUND: Thrombo-inflammation is central to COVID-19-associated coagulopathy. TF (tissue factor), a driver disordered coagulation and inflammation in viral infections, may be a therapeutic target in COVID-19. The safety and efficacy of the novel TF inhibitor rNAPc2 (recombinant nematode anticoagulation protein c2) in COVID-19 are unknown. METHODS: ASPEN-COVID-19 was an international, randomized, open-label, active comparator clinical trial with blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
1
Order By: Relevance
“…9 More recently, NAPc2 was also evaluated in COVID19 and showed anticoagulant efficacy without apparent interference with antiviral immunity. 69 Whereas our study clearly defines the physiological importance of the TF-FVIIa-PAR2 axis in CVB3 infection, the phenotype differs from what was reported by Weithauser et al in PAR2 −/− mice. The investigators used the CVB3(N) strain to induce myocarditis and observed a reduction of viral load and myocardial inflammation.…”
Section: Discussioncontrasting
confidence: 76%
“…9 More recently, NAPc2 was also evaluated in COVID19 and showed anticoagulant efficacy without apparent interference with antiviral immunity. 69 Whereas our study clearly defines the physiological importance of the TF-FVIIa-PAR2 axis in CVB3 infection, the phenotype differs from what was reported by Weithauser et al in PAR2 −/− mice. The investigators used the CVB3(N) strain to induce myocarditis and observed a reduction of viral load and myocardial inflammation.…”
Section: Discussioncontrasting
confidence: 76%
“…With the recent phase 2 clinical trials of the use Factor XI inhibitors 92 , 93 and tissue factor inhibitors for anticoagulation therapy and thromboprophylaxis, 94 the list of medications in the “DOAC” will inevitably continue to expand. As the list of available anticoagulation medication grows and eventually become available for clinical use, it is in the best interest of the general patient population to develop and formalize guidelines and testing strategies, to improve anticoagulation stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…The ASPEN-COVID-19 trial (Assessing Safety, Hospitalization and Efficacy of rNAPc2 in COVID-19) compared the effect of 8 days of treatment with recombinant NAPc2 to heparin (low molecular weight or unfractionated) on the activation of coagulation in patients with COVID-19. 38 Recombinant NAPc2 reduced plasma TF activity by 20.3%. However, it should be noted that measurement of TF in plasma is inferior to measurement of TF in isolated EVs, 37 and this low level of reduction may not accurately reflect the anticoagulant activity of rNAPc2.…”
Section: Effect Of Inhibition Of the Tf:fviia Complex On Activation O...mentioning
confidence: 96%